JUDICIAL CONTROL OF FOREIGN ARBITRAL AWARDS IN INDONESIA - Sitorus, Winner (Indonesian Journal of International Law, 2017)
The enforcement of foreign arbitral awards has been recognized and accepted internationally through the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards. However, the Convention also allows the court where the enforcement is sought to refuse the enforcement of an award. This kind of judicial control is very important. However, it should be conducted in accordance with the refusal grounds stipulated in the Convention. The refusal grounds are restrictive and should be interpreted narrowly. The use of other grounds other than and/or overly broad interpretation of the refusal grounds provided by the Convention will make it inefficient, which is from the outset the aim was to ease the recognition and enforcement of a foreign arbitral award in Contracting Parties of the Convention. This paper discusses the implementation of judicial control of foreign arbitral awards in Indonesia. It seeks to find out whether the judicial control of foreign arbitral awards in Indonesia has been in line with the requirements of the New York Convention. It finds that judicial control of foreign arbitral awards made by Indonesia's judiciary sometimes could be considered not in line with the requirements of the New York Convention.